PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KUALITAS LABA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Fauziah, Fitri Ella; Marissan, Ichwan (JURNAL AKUNTANSI DAN AUDITING, 2014)
This research is motivated by the growing environmental issues. Guidelines for good corporategovernance requires companies to create checks and balances, enforcing transparency andaccountability, as well as promoting corporate social responsibility for the survival of thecompany (KNKG, 2006). Disclosure of corporate social responsibility has a short-term goalis to minimize earnings management, while long-term goal is to build a good relationship withstakeholders. Research relating to the relationship between corporate social responsibilitywith diverse earnings quality. Research related to the relationship between corporate socialresponsibility with earnings quality is diverse, therefore, this study adds corporate governance asa moderating variable. This study aims to provide empirical evidence regarding the relationshipbetween corporate social responsibility and quality of earnings with corporate governance as amoderating variable. This study uses independent directors and audit committee as a proxy forcorporate governance mechanism, while earnings management or a proxy of earnings quality.The analysis technique used in the study is to use Moderating Regression Analysis (MRA) andresidual test. This study uses secondary data such as financial statements and annual report nonfinancialcompanies listed on the Indonesia Stock Exchange for the period 2010-2012. The resultsshowed that the hypothesis of one and two hypothesis is accepted while the third hypothesis isnot accepted.